Approximation to the nutritional contribution of the ordinary urban diet in Vitoria (Alava) in the transit from the 18th century until 19th century based on the hospital diets - Manuel Ferreiro Ardións; Karmele Díaz de Otazu Viteri (Universidad de Alicante, 2014)
Given the fact that hospital diets could be similar to a prototype belonging to urban artisans' ordinary diet lasting from the Ancient Regime to contemporaneity, five hospital diets have been analysed in the city of Vitoria (Spain) in order to determine if the caloric intake and the macronutrient intake could pose a risk factor in the acquisition, course and convalescence of infectious diseases according to the proposal of Livi Bacci. Conclusion the end result is all diets that were analysed caloric needs at the expense of consumption of bread, which makes this food a key factor in the appearance of an immunological risk caused by malnutrition. As a secondary effect, these has been an increase in the consumption of meat as compared to what bibliographic sources and the lack of potatoes in the ordinary diet prior to 1826 has been proved.